Pathogenesis of neoplasia - Arends, Mark (Henry Stewart Talks, 2024)
Oncogenes, Tumour suppressor genes (TSGs), Retinoblastoma, p53 “guardian of the genome”, Genetic instability, DNA and chromosome alterations, Cell death and apoptosis, Cancer diagnosis, Invasion and metastasis, Hallmarks of cancer